Egg quality and endoparasite prevalence in free range chicken farming in Apodi and Mossoró, Rio Grande do Norte, Brazil (Research, Society and Development, 2020)
The objective of this work was to assess the production quality of free-range eggs in the municipalities of Apodi and Mossoró, in the state of Rio Grande do Norte, Brazil. The microbiological and physical quality of the eggs and the endoparasite prevalence in the chickens were used as parameters. The egg microbiological evaluation consisted of the detection and quantification of total and thermotolerant coliforms, mesophilic bacteria, Staphylococcus aureus, and Salmonella sp. The eggs were classified according to their weight, yolk color, yolk pH, albumen pH, Haugh unit, yolk index, and shell thickness. The parasitological analyses consisted of collection of fresh excreta and application of the spontaneous sedimentation technique by the Hoffmann method and the Faust flotation method to identify the parasites. All egg samples were negative for total and thermotolerant coliforms, mesophilic bacteria, and Salmonella sp. Regarding the physical quality, the eggs presented good yolk pigmentation and good internal and external quality. Regarding the parasitic load of the chickens, the presence of Eimeria sp. and Heterakis sp. was significantly higher in months with average precipitation greater than 100 mm; and in months with average relative air humidity above 80%, there was prevalence of Ascaris sp. parasites.